2020
DOI: 10.1177/1054773820940873
|View full text |Cite
|
Sign up to set email alerts
|

In the Shadows of Patients with Upper Gastrointestinal Cancer: An Interview Study with Next of Kin about Their Experiences Participating in Surgical Cancer Care

Abstract: The study aimed to explore the experiences of participation among the next of kin of patients who had surgery for upper abdominal tumours. This study had a qualitative research design and data were analysed by thematic analysis. Eleven qualitative interviews were conducted with next of kin to patients who had surgery for liver, bile duct or pancreatic malignancy. The following themes emerged: from the shadows to an important role and an inviting and inhibiting environment for participation. Next of ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…By increasing the dialogue and exchange of information between health care professionals and patients, participation can occur, which in turn can reduce the incidence of postoperative complications and prolong the length of care (Boulding et al, 2011; Lee et al, 2018). It is also valuable to include the next of kin of this group of patients, as a study has shown that the next of kin are hidden by the patient but should support the patient in different ways after discharge (Ibrahim et al, 2020). Compliance with standardised postoperative care is lower than that with preoperative and intraoperative care.…”
Section: Discussionmentioning
confidence: 99%
“…By increasing the dialogue and exchange of information between health care professionals and patients, participation can occur, which in turn can reduce the incidence of postoperative complications and prolong the length of care (Boulding et al, 2011; Lee et al, 2018). It is also valuable to include the next of kin of this group of patients, as a study has shown that the next of kin are hidden by the patient but should support the patient in different ways after discharge (Ibrahim et al, 2020). Compliance with standardised postoperative care is lower than that with preoperative and intraoperative care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the care of family members can be improved concerning their involvement in surgical care. Family members have an important psychosocial role in surgical care but still must struggle to be involved (Ibrahim et al, 2020). Additionally, healthcare professionals do not prioritize tasks that support participation due to a stressful work environment (Andersson et al, 2021).…”
Section: Backg Rou N Dmentioning
confidence: 99%